Analisis Pengaruh Platform E-Commerce terhadap Perilaku Konsumen melalui Kualitas Produk - Melia Putri; Ervynasari, Apriliana (Sehati Abdimas, 2024)
This study aims to examine the relationship between e-commerce, consumer behavior, and product quality, with a focus on how product quality mediates the relationship between e-commerce and consumer behavior. In the context of e-commerce, product quality is an important factor influencing consumer purchasing decisions, especially since consumers cannot see or feel the product directly. Therefore, information such as reviews, ratings, and product descriptions on e-commerce platforms play a significant role in shaping consumer opinions on product quality. A quantitative approach was used in this study, with primary data collected through questionnaires distributed to 100 student respondents from the Faculty of Economics and Business, Universitas Muhammadiyah Surakarta (FEB UMS). The data collection method used was survey sampling, and analysis was carried out using the T-statistic test to test the relationship between variables. The results of the study showed that e-commerce had a significant influence on consumer behavior with a coefficient of 0.170, although the influence was relatively weak. E-commerce also had a significant effect on product quality (coefficient 0.669), and product quality was proven to have a large impact on consumer behavior (coefficient 0.795). In addition, product quality significantly mediates the relationship between e-commerce and consumer behavior (mediation coefficient 0.532). This finding suggests that improving product quality on e-commerce platforms can strengthen changes in consumer behavior, both directly and through the influence of better product quality.